An analysis of conventional and modern packaging approaches for cut flowers: a review article - Rashed, Nahed M.; Memon, Saba Ambreen; Turki, Saleh M. Al; Shalaby, Tarek A.; El-Mogy, Mohamed M. (Frontiers in Plant Science, 2024)
Fresh-cut flowers are considered to be one of the most delicate and challenging commercial crops. It is important to take into consideration how to minimize loss during storage and transportation when preserving cut flowers. . Many impinging (bad effect) forces can interact to shorten the vase's life. In the flower industry, effective methods need to be developed to extend freshly cut flowers' life. Fresh-cut flowers' vase life can be shortened by a variety of interlocking causes. The flower industry must develop new techniques to extend the vase's lifespan. This review provides comprehensive, up-to-date information on classical, modified atmosphere packaging (MAP), and controlled atmosphere packaging (CAP) displays. This review provides comprehensive, up-to-date information on classical, modified atmosphere packaging (MAP), and controlled atmosphere packaging (CAP) displays. According to this review, a promising packaging technique for fresh flowers can be achieved through smart packaging. A smart package is one that incorporates new technology to increase its functionality. This combines active packaging, nanotechnology, and intelligence. This technology makes it easier to keep an eye on the environmental variables that exist around the packaged flowers to enhance their quality. This article offers a comprehensive overview of creative flower-saving packaging ideas that reduce flower losses and assist growers in more effectively handling their flower inventory. To guarantee the quality of flowers throughout the marketing chain, innovative packaging techniques and advanced packaging technologies should be adopted to understand varied package performances. This will provide the consumer with cut flowers of standard quality. Furthermore, sustainable packaging is achieved with circular packaging. We can significantly reduce packaging waste's environmental impact by designing reused or recyclable packaging.